Durability of AZ31 magnesium biodegradable alloys polydopamine aided. Part 2: Ageing in Hank's solution - Anna Carangelo; Annalisa Acquesta; Tullio Monetta (Journal of Magnesium and Alloys, 2019)
Magnesium alloys are candidates as biodegradable medical materials due to their biocompatibility and favorable mechanical properties. Unfortunately, the high corrosion rate in physiological media and the release of hydrogen, limit their widespread use in biomedical applications. In this work, an intermediate coating based on polydopamine (PDOPA), between Mg substrate and an organic coating, was used to decreasing the degradation rate of AZ31 magnesium alloy, during the long-term exposure in simulated body fluid. Electrochemical Impedance Spectroscopy measurements were carried out to study the corrosion resistance of samples. Results demonstrated that the PDOPA interlayer determined the reduction of the substrate degradation rate. The results were interpreted supposing a synergistic effect which occurred when PDOPA and the organic coating were used together. Keywords: Polydopamine, AZ31, Magnesium alloy, Electrochemical characterization, Degradation rate